Iterative addition of carbon nucleophiles toN,N-dialkyl carboxamides for synthesis of α-tertiary amines - Chen, Jiahua (2022)
A protocol for the synthesis of α-tertiary amines was developed by iterative addition of carbon nucleophiles toN,N-dialkyl carboxamides. Nucleophilic 1,2-addition of organolithium reagents to carboxamides forms anionic tetrahedral carbinolamine (hemiaminal) intermediates, which are subsequently treated with bromotrimethylsilane (Me3SiBr) followed by organomagnesium (Grignard) reagents, organolithium reagents or tetrabutylammonium cyanide, affording α-tertiary amines. Employment of (trimethylsilyl)methylmagnesium bromide as the 2ndnucleophile allowed for aza-Peterson olefination of the resulting α-tertiary (trimethylsilyl)methylamines with acidic work-up, resulting in the formation of 1,1-diarylethylenes.